The effects of experimentally-induced fatigue on gait parameters during obstacle crossing: A systematic review - Chardon, M. [UNESP] (2022)
Striking an obstacle while walking can be dangerous, reflecting the higher risks of losing one's balance, tripping and falling. Particular situations during which internal resources are limited, such as in a fatigued state, may impair performance when crossing obstacles, enhancing the risks of falls or accidents. Our goal was thus to review the effects of experimentally-induced fatigue (EIF) on gait parameters during obstacle crossing by healthy individuals. We systematically searched PubMed and Web of Science databases using ‘fatigue’, ‘obstacle crossing’ and their equivalent terms to extract data from studies investigating this domain. Nine studies were found. First, EIF-related effects on kinetics, EMG and obstacle contacts have been poorly studied. Second, consistent and inconsistent results were found in the kinematic outcomes after EIF. Consistent results included reductions in stride duration and increased step width. Inconsistent results included gait velocity (no-effect vs increased), leading and trailing-foot vertical clearance (reduced vs increased) and horizontal distance from foot to the obstacle before obstacle avoidance (no-effect vs increased). These findings should be interpreted cautiously, however, due to the heterogeneity of the obstacle crossing and EIF protocols.